Alterações na topografia e tomografia corneal e na morfometria palpebral em pacientes com espasmo hemifacial tratados com toxina botulínica-A - Osaki, Teissy Hentona [UNIFESP] (2016)
Purposes: 1) to evaluate possible corneal topographic and tomographic changes, in addition to eyelid morphometric changes in affected and normal contralateral eyes of patients with hemifacial spasm (HFS) treated with botulinum-A toxin (BTX-A); 2) to evaluate possible eyelid morphometric changes in affected and normal contralateral eyes of patients with HFS treated with BTX-A; 3) to compare two types of corneal imaging systems (Placido system versus Scheimpflug system) to evaluate corneal topographic parameters in patients with hemifacial spasm. Methods: Changes in corneal topographic and tomographic (magnitude of corneal astigmatism and steepest keratometry) and eyelid morphometric (palpebral fissure and interpalpebral surface area) parameters were evaluated in patients with hemifacial spasm during a complete treatment cycle (before, 15 days, two, three and four months) after BTX-A (Botox®, Allergan, Irvine, EUA) applications in the affected hemiface. For eyelid morphometric analysis, we used the Image J software. For corneal topographic analysis, Placido system (ATLAS; Carl Zeiss Meditec, Dublin, CA) was used, and for corneal tomographic evaluation, we used the Scheimpflug system (Pentacam Oculus, Inc., Berlin, Germany). Results: Twenty-four HFS patients were treated with BTX-A. On the normal hemiface, before treatment, palpebral fissure (PF), interpalpebral surface area (ISA), steepest K and corneal astigmatism (Placido system/ Scheimpflug system) measurements were: 8,7 ± 1,98 mm, 122,09 ± 39,37 mm2, 44,99± 1,45/ 44.89±1.33 D and 0,9 ± 0,64 D/ 0.87±0.87 D, respectively. No significant changes were observed in eyelid and corneal parameters over the four months on the normal hemiface. On the affected hemiface, before treatment, palpebral fissure (PF), interpalpebral surface area (ISA), steepest K and corneal astigmatism (Placido system/ Scheimpflug system) measurements were: 5,5 ± 1,77 mm, 67,68 ± 28,49 mm2, 46,91 ± 3,57 D/ 45.40±1.37 D, 2,63 ± 2.46D/ 1,27 ± 0,88 D, respectively. There was a significant increase in PF and ISA (8,36 ± 1,91 mm and 115,92 ± 34,44 mm2, respectively at 15 days; 8,18 ± 1,80 mm and 112,22 ± 33,57 mm2, respectively at 2 months, and 7,27 ± 1,65 mm and 95,48 ± 27,80 mm2, respectively at 3 months), and a significant reduction in steep K and corneal astigmatism (45,14 ± 1,20 D and 1,01 ± 0,58 D, respectively at 2 months, and 45,64 ± 1,77 D and 1,36 ± 1,31D, respectively at 3 months), when evaluated by Placido system, on the affected hemiface. Scheimpflug system did not detect changes in the steepest keratometric reading over the four months. This system detected significant reductions in corneal astigmatism values only at 15 days (1,16 ± 1.16D; p = 0,02) and at 4 months (0,91 ± 0,59; p = 0,03). Both the lid morphometric and the topographic corneal parameters tended to return to baseline values four months after application of BTX-A. Comparison between corneal topographic parameters, obtained with Placido system, between both affected and normal eyes showed statistically significant differences between both eyes before and four months after treatment. Steep K (46.91± 3.57 D) and astigmatism values (2.63± 2.46 D) were significantly higher in affected eyes of HFS patients than in non-affected eyes (44.99±1.45 D and 0.90±0.64 D) before treatment (p=0.001 for steep K and p=0.0003 for astigmatism). Astigmatism values were also were significantly higher in affected eyes (1.42±0.83D) than in non-affectted eyes (0.91±0.64D) at four months (p=0.006). Differences between both eyes tended to reduce during the BTX-A period of action. Conclusions: 1) Treatment with BTX-A in patients with HFS led to temporary corneal topographic changes on the affected eye during BTX-A period of action. Corneal tomographic parameters did not show a so discernible pattern reflecting BTX-A period of action; 2) Treatment with BTX-A in patients with HFS also led to temporary eyelid morphometric changes on the affected eye during BTX-A period of action; 3) Corneal changes on the affected side were best detected with Placido system than with Scheimpflug system.